Revitalization of Library and Administration (REVPUS) for Increasing Reading Interest State Elementary School Students Botok Magetan - Laili Arin Ramadhani; Aprillia Sinda Dinningrum; Safira Adara Khairunnisa (Journal of Dedication in Community, 2024)
The Library Revitalization and Administration Program (REVPUS), which was carried out at SD Negeri Botok, Karas District, Magetan Regency, aims to increase students' interest in reading and knowledge insights through reviving the library by rearranging facilities and student involvement in library management. In its implementation, students in grades 4, 5, and 6 are child librarians who manage the library administration system and are involved in book-lending activities. The revitalization includes the renovation of library rooms that were previously unmaintained, the grouping of books according to categories and levels of difficulty, and the addition of creative designs to increase the attractiveness of the library. In addition, open reading classes involving students in reading and borrowing books are also held to encourage increased interest in reading. The evaluation of the program through a questionnaire showed positive results, with high responses from teachers and students regarding the library's comfort, orderliness, and attractiveness. Despite facing obstacles such as a lack of book collections and the initial condition of the library being poorly organized, this problem was successfully overcome by rearranging shelves and adding relevant books. To ensure sustainability, this program requires a more varied procurement of books and active support from schools and communities.